CO2 photoreduction with water: Catalyst and process investigation. (December 2015) - Olivo, A.; Trevisan, V.; Ghedini, E.; Pinna, F.; Bianchi, C.L.; Naldoni, A.; Cruciani, G.; Signoretto, M.
Graphical abstract: Highlights: Evaluation of photocatalytic activity in CO2 reduction with H2 O in CH4 production. Optimization of a synthesis route of N-doped titania photocatalysts with both CuO as co-catalyst. Study of the influence of the amount of metal dopants on photoactivity and selectivity. The co-presence of Cu and N in the TiO2 systems enhance the methane production. The best catalytic performances have been obtained with a small copper amount (0.2 wt.%). Abstract: Economic development should not be separated from the concept of sustainability. The goal can be pursued by means of technologically advanced materials and processes that enable environmental protection. Carbon dioxide photoreduction using water as reducing agent could be a green and effective way to pursue this aim and titania is a good photocatalyst for this reaction. In this work the performances of N doped CuO–TiO2 photocatalysts in gas phase CO2 reduction have been studied. We have focused the attention on both the catalysts design and the process optimization. We have investigated, in particular, the effect of the presence of nitrogen and copper amount on the final catalysts performances. In order to learn high control of the catalytic process and to manage productivity and selectivity, by operating in very mild reaction conditions, the last part of the work has been centered on tuning the process parameters (CO2 /H2 O ratio). It has been observed that the CH4 formation is sensitive to copper amount and that exists a close correlation between the catalytic behavior and the reagents ratio.